Health Information System with Management on Backend Website and View on Frontend Android Application (HealthyGO) - King, Tan Hong; Abdulla, Raed; Shaikh, Tanveer Khaleel (Journal of Applied Technology and Innovation, 2020)
Health is one of the most important part of our life, without a good health we cannot perform things that we like such as exploring, socializing, and more. This research will discuss about why the proposed system “Health Information System with Management on Backend Website and View on Frontend Android Application” is needed and what have been done by the developer to achieve the requirements of the proposed system.